Correlation Between Family Support And Self-Care Management In Post-Stroke Patients - Nurul Laili (International Journal of Public Health, 2025)
Post-stroke condition is a neurological dysfunction condition that has an impact on changes and decline in body condition for a fairly long period of time. The need for support during recovery and rehabilitation by the family is very much needed by post-stroke patients in managing themselves to optimize their well-being and quality of life. The purpose of this study was to determine the relationship between family support and self-care management in post-stroke patients. The design of this study was correlational using a cross-sectional approach. A population of 23 respondents with purposive sampling obtained 21 samples. The measuring instrument used was a questionnaire and data analysis using the Spearman rank test. The results of the study showed that almost half of the respondents (47.8%) had good family support, and almost half of the respondents (47.8%) had good self-care management. The results of the statistical test from the Spearman's rho test showed a P value of 0.0001 <α 0.05, so it can be concluded that there is a positive (unidirectional) and very strong relationship (r = 0.870) meaning that the better the family support provided by the family, the stronger the self-care management in post-stroke patients. Family support is a health component that influences a person to improve their health status and quality of life.